2020
DOI: 10.1111/jfbc.13137
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of flavonoids from Musa acuminata Colla (Simili radjah, ABB) and the in vitro inhibitory effects of its leaf and fruit fractions on free radicals, acetylcholinesterase, 15‐lipoxygenase, and carbohydrate hydrolyzing enzymes

Abstract: Musa species are used traditionally for the management of many diseases. The study evaluated and compared anticholinesterase, anti‐inflammatory, antioxidant, and antidiabetic activities of Musa acuminata (Simili radjah, ABB) fruits and leaves fractions and characterized the bioactive compounds using HPTLC‐HRMS and NMR. Leaf fractions gave the higher biological activities than the fruit. Ethyl acetate fraction of the leaf had the highest total phenolic content (911.9 ± 1.7 mg GAE/g) and highest 2,2‐diphenyl‐1‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…TFC in TCEA was found to be the highest which is in accordance with the fact that the sample contains the highest TPC. It is believed polyphenols, including flavonoids, have a strong affinity for semipolar solvents, including ethyl acetate [36,39]. However, its difference to TFC from other samples is not as significant as in TPC.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%
“…TFC in TCEA was found to be the highest which is in accordance with the fact that the sample contains the highest TPC. It is believed polyphenols, including flavonoids, have a strong affinity for semipolar solvents, including ethyl acetate [36,39]. However, its difference to TFC from other samples is not as significant as in TPC.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%
“… Compounds listed in the Table were found in (1) total extract of leaves MA , (2) Pesudostem, and (3) Fruit Peels, (a) compounds compared with literature 7 , 40 43 , (b) compounds identified from Standard Authentic compound Quantitative with HPLC (conc. as µg/g), (c) compounds identified from NMR , (d) compounds identified from DataBase (MS-Dial, KNApSAcK , Metlin, and RIKEN ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with Oresanya et al . 43 .
Figure 3 In vitro IC 50 DPPH and ABTS antioxidant activity of different plant parts of Musa acuminata extracts.
…”
Section: Resultsmentioning
confidence: 99%
“…Bananas ( Musa acuminate ) are also very popular with significant uses of the leaves and fruits for food and medicinal purposes. Solvent extraction of the banana leaf and fruit identified the ethyl acetate fraction as the most active AChE inhibitor with IC 50 values of 404.4 and 478.2 µg/mL, respectively [36]. This may be due to differences in the level of phytochemicals as it was reported that the total phenolic contents of leaves and fruit were 85.4–911.9 and 12.0–70.2 mg GAE/g, respectively.…”
Section: Food‐derived Polyphenolic Compoundsmentioning
confidence: 99%